Socio-Economic Identity Founding: Experience of Youth Engaged in Unorganized Sector. - Kiran Chandran; Jose Antony (Journal of Social Work Education and Practice, 2023)
Identity is the way one individual define his or her self as a being in a given context through the expressions of self-concept and responses to the question ‘who’ and ‘what’ an entity constructs with himself or itself. Identity can be understood by a plurality of identities present in the environment, it may vary according to the social conditions and different social institutions because it is an evolving and evolved reality. In this study, the formation of identity is focused according to the young population engaged in occupational activities inside the unorganised sector for making their life. The youth labour market is expanding according to the changing demands of employment. Literacy and level of education are increasing among the Indian youth population, but the lack of opportunities of getting a job in the formal sector still challenging due to the socio-economic disparities. The study shows the youth can attain a better social identity by getting a better education, a good job according to the education, fair income, social status, career options, etc. The identity of the sector they are engaged as their profession or occupation give them an augmentation with their identity formation efforts. But the experiences of the youth engaged in the unorganised sectors though may be high yielding is not very supportive in making their identity empowered.  The growing population is a hold back for the youth to achieve these goals in life. In addition to the factors like dependency, dismal ownership of assets, lack of proper skill training etc. Really influence their formation of identity. Persons who are engaged in self-employment and employed in private enterprises cling to a better social identity than the other major types of unorganised sector jobs like agriculture, small scale business etc. Majority of the youth engaged in the unorganised sector share a feel that they are not paid according to their qualification and skill. The study found social and economic identity closely attached to the occupation, income and standard of living of an individual. The paper is explaining the formation process of the socio-economic identity of the youth in Kerala engaged with the occupations in the unorganised sectors.​